Turnover intention among Gen Y employees at 8 Avenue Business Centre, Seksyen 8 / Nor Shazleen Nor Azim - Nor Azim, Nor Shazleen (Faculty of Business and Management, 2018)
Turnover intentions is crucial to know in order to help the organizations to minimize it. This is because it will affect the organizations as the organizations invest vast amount to the human capital and it will eventually affect the productivity of the employees as soon they have the intention to leave the organization. This study identifies the turnover intention among Gen Y employees in private sector at 8 Avenue Business Centre, Seksyen 8. The independent variable on this study are organizational commitment, job stress and job satisfaction. Meanwhile, the dependent variable is Turnover Intention among Gen Y. Data of this study were collected through the questionnaires that were distributed to the respondent around 8 Avenue Business Centre, Seksyen 8. Then, data were analyzed by using Statistical Procedure Social Science (SPSS). The sampling technique that used in this study is convenience sampling. Total of the questionnaire that has been distributed is 100 and all questionnaires had been collected. The result of this study revealed that job stress and job satisfaction have positive significance influence on turnover intention among Gen Y employees in private sector at 8 Avenue Business Center, Seksyen 8. Meanwhile, organizational commitment have negative significance influence on turnover intention among Gen Y employees in private sector at 8 Avenue Business Center, Seksyen 8.